Comparison of Global Rating Assessment Between Examiners and Simulated Patients on Communication Skills with OSCE Scores: Perbandingan Penilaian Global Rating Antara Penguji dan Pasien Simulasi Pada Keterampilan Komunikasi Dengan Nilai OSCE - Waty, Wenny; Hutagalung, Albert Rodney; Tih, Fen; Sanjaya, Ardo; Gunadi, Julia Windi (Universitas Mohammad Husni Thamrin, 2025)
Introduction: In the field of medical education, the evaluation process of communication and clinical skills training is known as Objective Structured Clinical Examination (OSCE). OSCE can be assessed using the global rating method, which is a method of subjective evaluation by examiners and standardized patients of student performance. Objective: The study aims to examine the relationship between the subjectivity of examiners and standardized patients in OSCE scores using the global rating method. Methods: The study involved 985 students from the Faculty of Medicine at Maranatha Christian University who participated in the Local OSCE from December 2021 until January 2022. Secondary data were analyzed using logistic regression in SPSS software and presented in tables and multivariate analysis. Results: The global rating assessment by examiners showed a significant relationship with OSCE scores (p<0.001), while the global rating assessment by standardized patients did not show a significant relationship with OSCE scores (p>0.05). This indicates that the evaluation by examiners has a greater influence on OSCE results compared to the assessment by standardized patients. Recommendations: More comprehensive training is needed for standardized patients in conducting assessments using the global rating method to minimize bias. Furthermore, future research is recommended to explore other factors that may influence OSCE assessments to improve the validity and reliability of the evaluation.